2008
DOI: 10.1016/j.bbr.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A new test paradigm for social recognition evidenced by urinary scent marking behavior in C57BL/6J mice

Abstract: Olfaction is a major sensory element in intraspecies recognition and communication in mice. The present study investigated scent marking behaviors of males of the highly inbred C57BL/6J (C57) strain in order to evaluate the ability of these behaviors to provide clear and consistent measures of social familiarity and response to social signals. C57 males engage in scent marking when placed in a chamber with a wire mesh partition separating them from a conspecific. Male mice (C57 or outbred CD-1 mice) showed rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 62 publications
(93 reference statements)
5
62
1
3
Order By: Relevance
“…That is, inbred mouse strains-especially the C57BL/6 mice that serve as the genetic background of most transgenic strains-appear to have been artificially selected for unusual social gregariousness so that they lack the preference for familiar vs. stranger typical of outbred and rederived wild mice. This gregariousness might be caused by the reduced olfactory differentiability of inbred mice (20), although we observed that C57BL/6 mice displayed high cooccupancy (82.3 ± 9.6%) even when the other member of the dyad was a stranger of a different strain (C3H/He). It is also clear that inbred mice can differentiate between familiars and strangers, because social phenomena such as emotional contagion have been shown to be more pronounced between C57BL/ 6 cagemates than between strangers (21).…”
Section: Discussionmentioning
confidence: 45%
“…That is, inbred mouse strains-especially the C57BL/6 mice that serve as the genetic background of most transgenic strains-appear to have been artificially selected for unusual social gregariousness so that they lack the preference for familiar vs. stranger typical of outbred and rederived wild mice. This gregariousness might be caused by the reduced olfactory differentiability of inbred mice (20), although we observed that C57BL/6 mice displayed high cooccupancy (82.3 ± 9.6%) even when the other member of the dyad was a stranger of a different strain (C3H/He). It is also clear that inbred mice can differentiate between familiars and strangers, because social phenomena such as emotional contagion have been shown to be more pronounced between C57BL/ 6 cagemates than between strangers (21).…”
Section: Discussionmentioning
confidence: 45%
“…Mus musculus is a social species that engages in high levels of reciprocal social interactions, communal nesting, sexual and parenting behaviors, territorial scent marking and aggressive behaviors [8][9][10] . Several tests have been developed to examine social behavioral in mice (reviewed in 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory stimuli play a predominant role in determining intraspecific social behaviors [30,32] and provide information for subsequent strategies such as approach towards or avoidance of encounters [5,33]. Odor cues from animals that have long-term infection and are immunologically challenged induces avoidance responses in healthy conspecifics [34].…”
Section: Discussionmentioning
confidence: 99%